The Relationship between Aeroallergen Sensitization and Chronic Cough in School-Aged Children from General Population - Myongsoon Sung (Hindawi Limited, 2021)
Objective. Determining sensitivity to allergens is an essential step in diagnosing children with allergic diseases. Chronic cough has remained poorly understood with causative triggers. The purpose of our study was to shed light on the relationship between sensitization to aeroallergens and chronic cough. Methods. This population-based study examined children (aged 7 years to 13 years) between June and July 2016. The 1,259 children, 72 of whom (5.7%) had a chronic cough, and 1,187 of whom (94.3%) did not (controls), completed the questionnaire, but 1,051 children completed skin prick tests (SPTs) with eight aeroallergens. Results. There were positive SPT results to at least 1 allergen in 549 children (52.2%). Sensitization to house dust mite (HDM) was most common (chronic cough=46.9%; controls=47.2%), followed by pollen (chronic cough=21.9%; controls=16.5%) in both groups, but there was no difference in allergic profile and sensitization to aeroallergen (P>0.05 for all comparisons). Multivariable analysis with adjustment for confounding indicated that children who were in sensitization to pollen had an increased risk of chronic cough (aOR=2.387; 95% CI: 1.115 to 5.111; P=0.025). Multivariable analysis with adjustment for confounding indicated that children who were exposed to current smoking (aOR=4.442; 95% CI: 1.831 to 10.776; P=0.001) and mold (aOR=1.988; 95% CI: 1.168 to 3.383; P=0.011) were associated with chronic cough. Conclusion. Sensitization to pollen should be considered as a potential contributing factor to the development of chronic cough in school-aged children.